2020
DOI: 10.1016/j.heliyon.2020.e05517
|View full text |Cite
|
Sign up to set email alerts
|

Farm household access to agricultural services in northern Ghana

Abstract: Access to agricultural services promotes agricultural production and livelihoods of smallholders in most developing countries. This study explores the factors affecting smallholders' access to agricultural services in northern Ghana. The study relied on survey data for the analysis. We estimated a multivariate probit model to assess the factors influencing access to agricultural services and a generalized Poisson regression model to evaluate the factors affecting the degree of access to these services. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…Results revealed that households involved only in agricultural activities (12%) are more efficient than those which had off-farm sources of income as well. This result reinforces the findings of Anang and Asante (2020) , Coelli et al. (2005) and Rahman and Rahman (2009) .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Results revealed that households involved only in agricultural activities (12%) are more efficient than those which had off-farm sources of income as well. This result reinforces the findings of Anang and Asante (2020) , Coelli et al. (2005) and Rahman and Rahman (2009) .…”
Section: Resultssupporting
confidence: 93%
“…The effect of migration status on technical inefficiency is found to be positive, which indicates that households in which any members of the family migrate outside the district tend to be less efficient (4%) in rice production. This finding is consistent with Anang and Asante's (2020) study of farm household access to agricultural services in northern Ghana. Nguyen et al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies found that farmers who had to repay the loan tend to urgently sell their products through alternative marketing channels ( Shiferaw et al., 2011 ; Mudege et al., 2015 ; Mathenge et al., 2020 ). Lack of cash revenue could negatively affect farmers' participation in cooperatives' activities, causing preferences to sell through intermediate traders more than through collective marketing ( Raya, 2014 ; Kanchanaroek and Aslam, 2018 ; Balgah, 2019 ; Anang and Asante, 2020 ; Mathenge et al., 2020 ; Pochanasomboon et al., 2020 ; Yanakittkul and Aungvaravong, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…(2015) , Hérique (2019) , Yanakittkul and Aungvaravong (2020) Perceived benefits X 14 Social benefits level Satisfaction level (1–5 continuous) + Petcho et al. (2019) , Anang and Asante (2020) , Kramol et al. (2020) X 15 Economic benefits level Satisfaction level (1–5 continuous) + Petcho et al.…”
Section: Methodsmentioning
confidence: 99%